Case report: Two sisters with a germline CHEK2 variant and distinct endocrine neoplasias - Vallera, Raphaelle D.; Ding, Yanli; Hatanpaa, Kimmo J.; Bishop, Justin A.; Mirfakhraee, Sasan; Alli, Abdel A.; Tevosian, Sergei G.; Tabebi, Mouna; Gimm, Oliver; Söderkvist, Peter; Estrada-Zuniga, Cynthia; Dahia, Patricia L. M.; et al. (Frontiers in Endocrinology, 2022)
Genetic testing has become the standard of care for many disease states. As a result, physicians treating patients who have tumors often rely on germline genetic testing results for making clinical decisions. Cases of two sisters carrying a germline CHEK2 variant are highlighted whereby possible other genetic drivers were discovered on tumor analysis. CHEK2 (also referred to as CHK2) loss of function has been firmly associated with breast cancer development. In this case report, two siblings with a germline CHEK2 mutation also had distinct endocrine tumors. Pituitary adenoma and pancreatic neuroendocrine tumor (PNET) was found in the first sibling and pheochromocytoma (PCC) discovered in the second sibling. Although pituitary adenomas, PNETs, and PCC have been associated with NF1 gene mutations, the second sister with a PCC did have proven germline CHEK2 with a pathogenic somatic NF1 mutation. We highlight the clinical point that unless the tumor is sequenced, the real driver mutation that is causing the patient’s tumor may remain unknown.